Sol-Gel Process for Anti-Corrosion Coatings - Bera, Saheli; Udayabhanu, G.; Narayan, Ramanuj; Rout, T.K. (Journal of Research Updates in Polymer Science, 2013)
This review paper summarizes the current state of the art of sol-gel technology for formulating anti corrosive protective coating. A brief description of the mechanism of sol-gel reactions, various parameters that influence the property of the final product and the course of the sol-gel reaction has been given. Different types of metal precursors that are extensively used in sol preparation and the advantages and disadvantages have also been mentioned in brief. Surface chemistry of sol-gel matrix and various stabilizing and destabilizing forces that are active on the surface of colloidal particles have also been discussed. Problems related to obtaining good quality product with uniformly distributed concentrations have been outlined. Possible pathways for further improvement of anti-corrosive properties of the coating have been described, such as incorporation of various types of additives into the sol matrix prior to coating. As a whole the present study summarizes the superiority and benefits of organic-inorganic hybrid coatings using sol-gel technique and having good protective and anti-corrosive properties.